From "Carmen" to Gypsy disco polo: the Gypsy myth in the modern European musical culture = Od "Carmen" po cygańskie disco polo: mit cygański w kulturze muzycznej Europy nowożytnej - Piotrowska, Anna G. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It can be claimed that modern European musical culture contributed to the crystalliza-tion and dissemination of a certain stereotype of a Gypsy person, and contributed to the creation of the highly romanticised Gypsy myth. The author of the paper - Anna G. Piotrowska, shows how 19th century operas, operettas or instrumental works helped to propagate the image of the stereotyped Gypsy, and ventures to prove that also pop music heavily draws on the same stereotype.
Keywords: Gypsy myth; Gypsies; carmen; mit cygański; Cyganie